Impact of a Multidomain Intensive Lifestyle Intervention on Complaints About Memory, Problem-Solving, and Decision-Making Abilities: The Action for Health in Diabetes Randomized Controlled Clinical Trial. (28th May 2018) - Espeland, Mark A; Dutton, Gareth R; Neiberg, Rebecca H; Carmichael, Owen; Hayden, Kathleen M; Johnson, Karen C; Jeffery, Robert W; Baker, Laura D; Cook, Delilah R; Kitzman, Dalane W; Rapp, Stephen R
Abstract: Background: Lifestyle interventions to reduce weight and increase activity may preserve higher-order cognitive abilities in overweight/obese adults with type 2 diabetes (T2D). Methods: Adults ( N = 5, 084) with T2D who enrolled in a randomized clinical trial of a 10-year intensive lifestyle intervention (ILI) compared with diabetes support and education were queried at baseline and repeatedly during follow-up for complaints about difficulties in memory, problem-solving, and decision-making abilities. Results: For those without baseline complaints, assignment to ILI was associated with lower odds that complaints would emerge during follow-up for decision-making ability (odds ratio [OR]=0.851, [95% CI, 0.748, 0.967], p=0.014), and, among individuals who were not obese, lower odds that complaints would emerge about problem-solving ability (OR=0.694 [0.510, 0.946]). No cognitive benefits from ILI were seen for individuals with baseline complaints about cognitive abilities. ILI may have exacerbated the severity of complaints about problem-solving ability during follow-up among individuals with baseline complaints and cardiovascular disease (OR=2.949 [1.378, 6.311]). Conclusions: A long-term multidomain ILI may reduce the likelihood that complaints about difficulties in higher-order cognitive abilities will emerge in T2D adults without pre-existing complaints. Among those with pre-existing complaints, the ILI did not prevent increases in complaint severity.